Wear and corrosion behaviour of titanium carbide reinforced metal matrix composites for automobile brake disc application. (28th August 2019) - Sivananth, V.; Karuppusamy, P.; Lingadurai, K.
The wear and corrosion behaviour of aluminium silicon (Al-Si) alloy with titanium carbide (TiC) were investigated in this article. Initially automobile brake discs of a passenger car were fabricated by stir casting method with 10 wt. % of TiC in Al-Si alloy. A small part cut from the brake shoe used as a pin to slide against MMC and Grey cast iron in dry condition. It was found from the results that the wear resistance and coefficient of friction for TiC reinforced MMC is better than iron. Experimental values of wear agree very closely with simulation results. Potentiodynamic polarisation measurements exhibits that the corrosion resistance decreased with increasing TiC weight percentage. However, the hardness of the samples was increased. SEM analysis showed more no. of corrosion spots in samples with 10 wt. % of TiC. XRD analysis revealed that the presence of reinforcement in matrix affect the corrosion rate.